Relationship between peatland water use and periodontal disease in Daha Selatan Subdistrict - Hidayah, Antung Nurul; Oktiani, Beta Widya; Azizah, Aulia (Majalah Kedokteran Gigi Indonesia, 2022)
Periodontal disease is one of the dental and oral health problems in Hulu Sungai Selatan Regency with a prevalence of gingivitis of 24.58% and periodontitis of 10.83%. One of the risk factors for periodontal disease is the use of peatland water. Peatland water has a low pH which can affect the colony of anaerobic bacteria in the oral cavity of the water users. Bacteria that cause periodontal disease are able to develop and survive in acidic conditions. This study aimed to analyze the relationship between peatland water use and periodontal disease in Daha SelatanSubdistrict. This was analytical research with a cross-sectional approach. The sampling technique used a simple random sampling technique with a total sample of 100 people (n = 100) who were residents aged 35-44 years in Daha Selatan Subdistrict. The results showed that the participants with high use of peatland water showedthe highest percentage (39%). In addition, there were 61% respondents who suffered from periodontal disease. ChiSquare test obtained a significance value of 0.022 (p < 0.05), showing that there was a relationship between peatland water use and periodontal disease. The risk of periodontal disease in the respondents who used peatland water in the high category was 4.167 times greater than in the respondents who did not use peatland water. It is essential to educate the general public about the effects that using peatland water can have on dental and oral health because there is a high prevalence of periodontal disease, which is caused by the widespread use of peatland water.